Developing multitarget coumarin based anti-breast cancer agents: synthesis and molecular modeling study - Fiby N. Takla; Waleed A. Bayoumi; Shahenda M. El-Messery; Magda N. A. Nasr (Scientific Reports, 2023)
Abstract A new series of 7-substituted coumarin scaffolds containing a methyl ester moiety at the C4-position were synthesized and tested for their in vitro anti-proliferative activity against MCF-7 and MDA-MB-231 breast cancer cell lines using Doxorubicin (DOX) as reference. Compounds 2 and 8 showed noticeable selectivity against MCF-7 with IC50 = 6.0 and 5.8 µM, respectively compared to DOX with IC50 = 5.6 µM. Compounds 10, 12, and 14 exhibited considerable selectivity against Estrogen Negative cells with IC50 = 2.3, 3.5, and 1.9 µM, respectively) compared to DOX with (IC50 = 7.3 µM). The most promising compounds were tested as epidermal growth factor receptor and aromatase (ARO) enzymes inhibitors using erlotinib and exemestane (EXM) as standards, respectively. Results proved that compound 8 elicited the highest inhibitory activity (94.73% of the potency of EXM), while compounds 10 and 12 displayed 97.67% and 81.92% of the potency of Erlotinib, respectively. Further investigation showed that the promising candidates 8, 10, and 12 caused cell cycle arrest at G0–G1 and S phases and induced apoptosis. The mechanistic pathway was confirmed by elevating caspases-9 and Bax/Bcl-2 ratio. A set of in silico methods was also performed including docking, bioavailability ADMET screening and QSAR study